Detection of mild cognitive impairment in people older than 65 years of age and its relationship to cardiovascular risk factors (DECRIVAM) - Agudo-Conde Cristina; Almanza-Guerra Tita J; Patino-Alonso María C; Mora-Simón Sara; Ladera-Fernández Valentina; García-García Ricardo; Perea-Bartolome M Victoria; Muriel-Diez M Paz; Rodríguez-Sánchez Emiliano (BMC Public Health, 2011)
Abstract Background Studies centered on the detection of cognitive impairment and its relationship to cardiovascular risk factors in elderly people have gained special relevance in recent years. Knowledge of the cardiovascular risk factors that may be associated to cognitive impairment could be very useful for introducing treatments in early stages - thereby possibly contributing to improve patient quality of life. The present study explores cognitive performance in people over 65 years of age in Salamanca (Spain), with special emphasis on the identification of early symptoms of cognitive impairment, with the purpose of detecting mild cognitive impairment and of studying the relationships between this clinical situation and cardiovascular risk factors. Methods/Design A longitudinal study is contemplated. The reference population will consist of 420 people over 65 years of age enrolled through randomized sampling stratified by healthcare area, and who previously participated in another study. Measurement: a) Sociodemographic variables; b) Cardiovascular risk factors; c) Comorbidity; d) Functional level for daily life activities; and e) Study of higher cognitive functions based on a neuropsychological battery especially adapted to the evaluation of elderly people. Discussion We hope that this study will afford objective information on the representative prevalence of cognitive impairment in the population over 65 years of age in Salamanca. We also hope to obtain data on the relationship between cognitive impairment and cardiovascular risk factors in this specific population group. Based on the results obtained, we also will be able to establish the usefulness of some of the screening tests applied during the study, such as the Mini-Mental State Examination and the 7 Minute Screen test. Trial registration ClinicalTrials.gov: NCT01327196